343 views
3 votes
What is the solution of this system of linear equations?

3y = x + 6

y – x = 3

2 Answers

7 votes
3y = x + 6
y = x + 3 Subtract:-

2y = 0 + 3
y = 3/2 = 1.5

Plug this value of y into the first equation:-

3(1.5) = x + 6
x = 4.5 - 6 = -1.5

Answer is x = -1.5, y = 1.5
User Chatar Singh
by
4.9k points
2 votes
3y = x + 6
y – x = 3 -----------> x=y - 3 (substitute in 1st equation)

3y = y - 3 +6
3y - y = 3
2y = 3
y = 2/3

x= y - 3 = 2/3 -3 = 2/3 - 9/3 = - 7/3

x= - 7/3, y = 2/3


User Joe Ho
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.